A rare Cypriot krater of the White Slip II style from Azekah - Yasʿur-Landau, Assaf; Oeming, Manfred (Israel exploration journal, 2014)
This article identifies a Cypriot krater found at Azekah in 2012 as a White Slip II type 2 krater, a very rare import to the Levant. Its rarity may be explained not only by the fact that such kraters were not mass-produced vessels intended for export like the WSII bowls, but also by their shape, which would look unfamiliar and strange to the Canaanite and thus would serve as an intercultural barrier to its use in a Canaanite feast.